Back to the Future : Postwar Reconstruction and Stabilization in Lebanon - Helbling, Thomas (Occasional Papers; Occasional Paper ;, 1999)
Following the 15-year civil war that started in 1975, Lebanon's government began the difficult task of economic stabilization and confidence building, on the one hand, and postwar reconstruction and development, on the other. The government led the reconstruction effort by formulating programs that aimed to rapidly rehabilitate the country's severly damaged infrastructure in preparation for private-sector-led growth over the medium term. At the same time, Lebanon introduced an exchange-rate-based nominal anchor policy to stabilize expectations and cut inflation. This paper analyzes the government's progress with the policies adopted.